KELEKATAN FIGUR AYAH DENGAN GAYA PACARAN PEREMPUAN GENERASI Z - Keisya Shaskia Dea Fanda,; Dewita Karema Sarajar, (Journal of Innovation Research and Knowledge, 2026)
This Study aims to examine the relationship between father-figure attachment and dating styles among Generation Z women in Indonesia, who are navigating a transition from collectivistic cultural values to digital modernity. Using a quantitative correlational design, the research involved 218 female respondent aged 17-25 years who completed an online questionnaire. The instruments used were the Adult Scale of Parental Attachment-Short Form (ASPA-SF) and the Love Attitudes Scales (LAS), both demonstrating high reliability (α = 0,977 and α = 0,955). Data analysis using the Spearman Rank correlation test yielded a coefficient value of ρ = 0,679 with p < 0,001, indicating a significant positive relationship between father-figure attachment and dating style. These findings suggest that strong emotional attachment to the father plays a crucial role in shaping healthier, more adaptive, and mutually respectful romantic relationship patterns. Theoretically, this study reinforces Bowlby’s attachment theory within the Indonesian cultural context, while practically, it provides a foundation for developing culturally grounded family counseling programs that emphasize emotional involvement of fathers to support the formation of healthy romantic relationship among young adult women.